Distributed fiber optic strain sensing in axially loaded glued-in steel rods in glued-laminated timber - Ernewein, Benjamin; Woods, Joshua E. (Construction & building materials, 2023)
•Glued-in rod connections instrumented with distributed fiber optic sensors (DFOS) were tested.•Strain sensors used to measure distributed strain profiles along the rod-adhesive and adhesive-timber interfaces.•Experimental strain distributions in good agreement with Volkersen theory.•Distributed strains from DFOS can be used for bond-slip measurement.•Challenges surrounding use of nylon-coated fiber optic cables for short bond lengths. The rise in popularity of mass timber structures globally has increased the demand for high-performance timber connections. Glued-in rod connections which are advantageous compared to other dowel-type connections because of their high strength and stiffness, have been the subject of extensive research in the literature; However, the lack of an in-depth understanding of their behavior and a uniform set of guidelines for their design continues to limit the use of glued-in rods in practice. To develop an improved understanding of the behavior of glued-in rod connections this paper examines, for the first time, the use of distributed fiber optic sensors to measure the complete strain distribution along the length of a glued-in rod connection. Axial pullout tests were conducted on twenty-five glued-in rod connections in glued-laminated timber with varying embedment lengths and glue-line thicknesses. Results of the study demonstrate the ability of fiber optic sensors to capture the full strain distribution along the length of the steel rod and along the epoxy-adhesive interface, enabling the study of localized behavior that would be difficult to measure using conventional strain gauges. In addition, results demonstrate the ability of distributed fiber optic strain sensors to infer axial stress and force distributions along the length of a glued-in rod connection, which are compared with theoretical distributions from the Volkersen model, as well as measure bond-slip behavior.